(untitled) (Development Service Industry Management, 2023)
The article is devoted to the justification and rationalization of the instrumental content of the marketing activity of domestic enterprises in the agrarian sector. Provisions characterizing the role and importance of agricultural marketing are defined, among which are highlighted: optimization of resource use and management of results; increase in farm income; expansion of markets; growth of the agricultural industry; introduction and distribution of new technologies; job creation; allowance to national income; value creation. It was determined that many factors should be considered in agribusiness when determining the marketing strategy, and the marketing complex as a strategy will positively affect the work of the enterprise. Twelve controllable marketing elements are outlined, which include the following components: product planning, pricing, branding, distribution channels, personal selling, advertising, promotions and promotions, packaging, display, service, delivery, research, and analysis. The difference between consumer and agricultural goods is substantiated, and the specifics of agricultural goods are determined, including the dependence of production on natural and biological factors, seasonality of production, predominance of wholesale sales; the need for processing, short consumption period, lack of ideal substitutes; lack of effective quality control mechanisms; the limited influence of the brand, advertising, after-sales service, fashion and style, emotional factors; low elasticity of demand. Certain aspects of state policy are revealed as an addition to the traditional Ps of the marketing mix for the sale of agricultural products; in particular, it is stated that the agricultural policy should be structured in such a way as to provide support to small farmers through projects of improvement, diversification, and sale of agricultural products.